PENGARUH CURRENT RATIO, DEBT TO EQUITY RATIO, RETURN ON EQUITY DAN EARNING PER SHARE TERHADAP HARGA SAHAM PADA PERUSAHAAN PERTAMBANGAN YANG TERDAFTAR DI BEI PERIODE 2009-2011 - Wardi, Jeni (Jurnal Akuntansi (Media Riset Akuntansi & Keuangan), 2015)
This study aims to look at the effect of the current ratio, debt to equity ratio, return onequity and earnings per share of the stock price on mining companies listed inIndonesia Stock Exchange Period 2009-2011. Companies that the sample was 14 of27 mining companies listed on the Stock Exchange in 2009-2011.The analytical method used is multiple regression analysis. Before the t test formultiple regression equation, performed first test the classical assumption ofnormality, autocorrelation, multicollinearity and heteroscedasticity. Once the data isfree from the classical assumption, then the hypothesis test using t test to see theeffect of each independent variable on the dependent variable partially.Based on the analysis, it is known that the only variable earnings per share aresignificant effect on stock prices. Meanwhile, current ratio, debt to equity ratio andreturn on equity is significantly not having any impact on stock prices. The coefficientof determination of 56.8% 43.2% where there are more changes in the dependentvariable that is influenced by other variables those are not included in this study.Keywords: stock price, current ratio, debt to equity ratio, return on equity, earningsper share.